An Astronomical Diary: or Almanack, For the Year of Christian Aera 1795. Being the third year after Bissextile, or Leap-Year; and the Nineteenth of the Independence of America, which began July 4th, 1776. - Low, Nathanael, 1792-1883. (Tufts University. Tisch Library., 2018)
12 leaves [Tisch Library copy is bound with an additional front and back cover sheet dated 1830, and contains handwritten annotations].